A 22-year-old woman with unexplained exertional dyspnoea - Internullo, M; Bonini, M; Marinelli, P; Perli, E; Cerbelli, B; Palange, P (Thorax, 2016)
[...]the age of 20, she practised regular non-competitive physical activity. Even though the majority of mitochondrial disorders have no specific treatment, 9 10 it has been reported that some forms may benefit from supplementation of carnitine, riboflavin and coenzyme Q10, as well as from programmes of physical training, leading to better exercise tolerance and to an improvement of symptoms. 8 11-13 It has been in fact suggested that the use of these precursors of coenzymes may result in a clinical response by stimulation of enzyme activity. 14 Riboflavin showed a beneficial effect in several patients with Complex I deficiency. 15 16 In three of those patients, a defect in Complex I activity was associated with normal carnitine levels in serum but decreased carnitine content in muscle, while four had low serum carnitine levels, suggesting the need of implementation. 17-19 Our patient reported a significant clinical improvement with reduced respiratory discomfort during exercise after 1 year of riboflavin and carnitine supplementation.